ANALISIS PENGARUH KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI SEKERTARIAT DPRD KOTA BATU MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Elvan Febrianto (Ma Chung Press, 2018)
This research was conducted in sekertariat DPRD Kota Batu in January 2017. Employee performance is considered high, can be seen from the increasing number of customers. The problems studied in this study is whether there is direct influence between leadership and work environment on employee performance, the influence of employee job satisfaction on employee performance. The purpose of this study is to identify and analyze the direct influence of leadership and work environment on employee performance, identify and analyze the effect of employee job satisfaction on employee performance. The population of this study is 50 people using Slovin formula. Methods of collecting questionnaire data, analysis methods are instrument test (validity test and reliability test), percentage descriptive analysis, classical assumption test and path analysis using SPSS 16.0 for Windows. The conclusion of this research is the improvement of employee performance achieved by improving leadership, work environment and employee job satisfaction. The suggestion of this research is to give bonus for employees who have achievement on their performance